(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Coarctation of the aorta is a congenital cardiac malformation that can go undiagnosed until old age with only hypertension as a marker of its presence because clinical signs can be subtle and overlooked if a complete physical exam is not performed. Long-term survival is exceptional in patients with untreated aortic coarctation. In this case report, we present a late diagnosis of aortic coarctation in a 45-year-old male. Our patient was relatively asymptomatic until he presented with exertional dyspnea and fatigue in his fourth decade of life. The patient was managed by surgery of aorta. After the 6 months follow-up visit, the patient was in good clinical condition. J Bangladesh Coll Phys Surg 2018; 36(1): 33-36